Bat fauna (Mammalia, chiroptera) from guarapuava highlands, Southern Brazil - Miranda, João M.D.; Silva, Luciana Zago da; Pressinatte-Júnior, Sidnei; Pereira, Luana de Almeida; Marchioro, Sabrina; Bélla, Daniela Aparecida Savariz; Carvalho, Fernando (Oecologia Australis, 2019)
Here, we present an updated list of bats fromGuarapuava highlands, center-southern of Paraná state, southern Brazil. This species list is based on four literature records (secondary data) and data from fieldwork (primary data) in three localities. All species recorded (primary and secondary data) were evaluated by the relative frequency and their conservation status were assessed. The species recorded from fieldwork were also evaluated by relative abundance. A beta diversity analysis was done to verify dissimilarities in the bat fauna among the seven localities. We recorded 28 species in the Guarapuava highlands (14 Vespertilionidae, 10 Phyllostomidae and 4 Molossidae), of which, eight are new records for the region. Sturnira lilium was the most abundant in three localities (primary data), and the most frequent species in all studies (primary and secondary data). Only four species were classified globally as “Near Threatened” or “Data Deficient”, nevertheless they were frequent in this region. The mean regional beta diversity was 0.72, what could be mostly explained by turnover (0.64) rather than by nestedness (0.08). The greatest species richness of the family Vespertilionidae is a common pattern in subtropical and temperate regions as in highlands and mountains. As turnover was the main component of the beta diversity, the communities seemed to be structured mainly by replacement of species among the studied localities. The Guarapuava highlands present a diverse bat fauna, however, this region requires more sampling effort to become well known. © 2019, Universidade Federal do Rio de Janeiro (UFRJ). All rights reserved.